Experiences of women in early marriages in rural Zimbabwe - Mutembedza, Tendai Elvis; Kessi, Shose (PINS-Psychology in Society, 2022)
This paper attempts to provide a nuanced analysis of the experiences of women in early marriages in rural Zimbabwe. It was guided by a decolonial social constructionist framework and inspired by a feminist lens that endeavoured to gain insight into the first-hand experiences of early marriage. In-depth narrative interviews were carried out with eleven women who experienced early marriages. The article addresses the marginalised voices of the women by providing space for them to share their stories and lived experiences within the context of their everyday lives. Research findings highlighted that there were diverse reasons for early marriages, mostly cultural and economic. However, such marriages were also characterised by various forms of abuse which resulted in the women having difficulties adjusting back into society after surviving these marriages. Findings also show that societal norms and beliefs continue to influence and shape the behavior and experiences of women in negative and detrimental ways through promoting early marriage practices.